Spermatozoa ultrastructure of two basal pilidiophoran nemerteans, Hubrechtella juliae and Sonnenemertes cantelli (Nemertea, Pilidiophora). (June 2020) - Chernyshev, Alexei V.; Neznanova, Svetlana Yu.; Yurchenko, Olga V.
Highlights: Spermatozoa of two basal nemerteans have been studied at the ultrastructural level. Both species have primitive spermatozoa with ovoid head and five mitochondria. Acrosomal complex of Sonnenemertes cantelli composed of multiple small vesicles. Abstract: Nemertea is a phylum of worms with a simple internal morphology; nemerteans' spermatozoon morphology can be used for their classification and phylogenetic analyses. The aim of the present study was to describe spermatozoa of the nemerteans Hubrechtella juliae and Sonnenemertes cantelli from the basal groups of the class Pilidiophora at the ultrastructure level. Both species have primitive ('compact-head' sensu Stricker and Folsom, 1998 ) spermatozoa with ovoid head and five mitochondria in the midpiece, but differ in the structure of acrosomal complex: in Hubrechtella juliae, the single lens-shaped acrosomal vesicle contains an area of moderate electron density not enclosed by a separate membrane; in Sonnenemertes cantelli, the acrosome shows a unique morphology and contains a few electron-dense vesicles with irregular shapes and positions and one more electron-lucent elongated vesicle. Such a pattern of the acrosomal complex organization is described for Nemertea for the first time. An assumption is made that the states "two or more mitochondria" and "posterior acrosomal ring component" may be synapomorphies of Hubrechtiiformes+Heteronemertea (class Pilidiophora), whereas "the posterior margin of the acrosomes forms an acrosomal ring component" is presumably an autapomorphy of the family Lineidae s.l. The results suggest that spermatozoa provide a useful source of characters for nemertean systematics.